2019
DOI: 10.1117/1.nph.6.1.015001
|View full text |Cite
|
Sign up to set email alerts
|

Denoising of neuronal signal from mixed systemic low-frequency oscillation using peripheral measurement as noise regressor in near-infrared imaging

Abstract: Functional near-infrared spectroscopy (fNIRS) is a noninvasive functional imaging technique measuring hemodynamic changes including oxygenated (O 2 Hb) and deoxygenated (HHb) hemoglobin. Low frequency (LF; 0.01 to 0.15 Hz) band is commonly analyzed in fNIRS to represent neuronal activation. However, systemic physiological artifacts (i.e., nonneuronal) likely occur also in overlapping frequency bands. We measured peripheral photoplethysmogram (PPG) signal concurrently with fNIRS (at prefrontal region) to extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 97 publications
3
13
0
Order By: Relevance
“…In summary, the high temporal resolution of fNIRS renders Granger-causality analyses of hemodynamic measurements possible and allows the comparison of different conditions provided that physiological parameters like aBP are controlled. In line with previous studies we demonstrated that (i) peripheral measurements of systemic hemodynamic processes can be used to correct functional connectivity estimates for physiological noise (Frederick et al 2012;Tong et al 2013;Sutoko et al 2019) and that (ii) ICA stenosis impairs functional network organization (Avirame et al 2015).…”
Section: The Change In Connectivity Between Resting and Breathing Consupporting
confidence: 91%
See 2 more Smart Citations
“…In summary, the high temporal resolution of fNIRS renders Granger-causality analyses of hemodynamic measurements possible and allows the comparison of different conditions provided that physiological parameters like aBP are controlled. In line with previous studies we demonstrated that (i) peripheral measurements of systemic hemodynamic processes can be used to correct functional connectivity estimates for physiological noise (Frederick et al 2012;Tong et al 2013;Sutoko et al 2019) and that (ii) ICA stenosis impairs functional network organization (Avirame et al 2015).…”
Section: The Change In Connectivity Between Resting and Breathing Consupporting
confidence: 91%
“…Furthermore, the PDC estimates (i.e. the connectivity corrected for aBP influences) were similar for the oxyHb, dxyHb, and CBSI data suggesting that the deviating results for the oxyHb-derived DC estimates were due to the higher susceptibility of the oxyHb measurement to physiological noise as previously reported (Obrig et al 2000;Zhang et al 2009;Kirilina et al 2012;Sutoko et al 2019). This again corroborates our finding that including the aBP signal in PDC estimation effectively controlled for bias induced by physiological noise.…”
Section: Adjusting Estimates Of Directed Connectivity For Arterial Blsupporting
confidence: 88%
See 1 more Smart Citation
“…The GLM method is a commonly known technique that allows the regression of short channels and that is relatively easy to implement. 12 , 38 , 45 47 It is known that the regression of different regressor signals may alter the shape of the recovered signal. 36 Therefore, we applied five regressor sets incorporating different assumptions on the spatial distribution of systemic interference.…”
Section: Methodsmentioning
confidence: 99%
“…Systemic artifacts are typically not constrained locally, but they affect the whole brain and extracerebral tissues, and are thus considered “global.” As a consequence, it is often assumed that global noise is distributed homogeneously over the entire scalp layer and thus that a single global signal can be used for the short-channel regression. 26 30 In contrast, it was repeatedly shown that scalp hemodynamics follow spatially heterogeneous patterns, 9 , 17 , 31 38 i.e., different short-channel signals are measured at different locations on the scalp. An additional complexity is observed when considering that the physiological artifacts also show frequency-dependent spatial variations, 36 with a noteworthy effect observed for the MW-frequency band (i.e., average time lags up to 2 s between ipsilateral head regions 36 ).…”
Section: Introductionmentioning
confidence: 99%